Wine tasting - Jackson, Ron. S. (Elservier Academic Press, 2017)
From OIV-award-winning author, Ronald S. Jackson, Wine Tasting: A Professional Handbook, Third Edition, is an essential guide for any professional or serious connoisseur seeking to understand both the theory and practice of wine tasting. From techniques for assessing wine properties and quality, including physiological, psychological, and physicochemical sensory evaluation, to the latest information on the types of wine, the author guides the reader to a clear and applicable understanding of the wine tasting process. With its inclusion of illustrative data and testing technique descriptions, the book is ideal for both those who train tasters, those involved in designing wine tastings, and the connoisseur seeking to maximize their perception and appreciation of wine.